Chemical Composition, In vitro Digestibility and Carbohydrate and Protein Fractions of Zuri Fodder at Different Days of Harvest - Ch. Ramesh Babu; K. Raja Kishore; D. Srinivas Kumar; K. Aswani Kumar (Indian Journal of Animal Nutrition, 2023)
In the present study, Zuri fodder was evaluated for chemical composition, oxalate content, in vitro digestibility and carbohydrate and protein fractions at different days (15, 20, 25,30 and 35) of harvest in its second cut. The mean CP content in Zuri fodder at different days of harvest was 14.68 per cent. The per cent oxalate content was highest (2.96) in the Zuri fodder harvested at 15 days as compared to mature fodder (1.65) at 35 days, with moderate content (1.89) at 30 days of harvest. The average in vitro digestibility (%) of DM and OM was 66.27 and 73.10, respectively, in Zuri fodder at different days of harvest. High lignin (% NDF), while low NSC (% DM) and starch (% NSC) were observed in Zuri fodder harvested at 35 days as compared to other stages. The mean NDICP and ADICP content (% CP) were 44.47 and 11.90, respectively, in Zuri fodder. The carbohydrate fractions (% CHO) revealed that carbohydrate fraction A (CA) was highest at 35 days of harvest, while fraction C (CC) was lowest at 15 days of harvest in Zuri fodder. Data on protein fractions (% CP) showed that protein fraction (PB2) was highest (17.71) at 35 days, while PB3 was highest (35.82) at 15 days of harvest in Zuri fodder. It was concluded that Zuri fodder harvested at 30 days contained moderate oxalate content, revealed better in vitro digestibility and carbohydrate and protein fractions which reflects high nutrient intake.